Penerapan Augmented Reality (AR) dalam Pembelajaran Fisika: Studi Kasus pada Materi Optik - Basir, Aditya Putra; Uding, Risnawati (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study aims to explore the application of Augmented Reality (AR) technology in physics education, focusing on optical materials. In the context of physics education, especially in Central Maluku, AR can serve as a solution to overcome the challenges of understanding abstract concepts such as light refraction, reflection, and light interaction with lenses. The use of AR allows students to view physical phenomena in a more concrete and interactive three-dimensional form, which helps enhance their understanding of optical materials that are difficult to grasp through conventional methods. This research employs a descriptive qualitative approach with semi-structured interviews and an exploratory approach with ten physics teachers in Central Maluku Regency. The findings indicate that although there are challenges such as limited devices and lack of teacher training, the use of AR has a positive impact on student engagement, material understanding, and learning outcomes. This study concludes that AR has great potential in improving the quality of physics education, although further support in terms of infrastructure and training is needed to optimize its implementation in schools.